Transparent high-performance SiOxNy/SiOx barrier films for organic photovoltaic cells with high durability - Lim, Ju Won; Jin, Chang Kyu; Lim, Keun Yong; Lee, Yun Jae; Kim, Sung-Ryong; Choi, Byung-Il; Kim, Tae Whan; Kim, Dong Ha; Hwang, Do Kyung; Choi, Won Kook (Elsevier BV, 2017)
The science and technology of organic electronics have made consistent progress. However, the long-term stability of organic devices is a critical issue that remains to be resolved. Encapsulation is a straightforward and practical means to protect organic materials from oxygen or moisture and thus improve air stability. Here, we report a high-performance flexible inorganic SiNx/SiOxNy hybrid barrier film for application in organic solar cells (OSCs). This hybrid barrier film shows average transmittance of 85.5% and a water-vapor transmission rate of 7.1x10 (5) g m (2) day (1). In OSCs comprising poly[4,8-bis[(2-ethylhexyl)oxy] benzo[1,2-b:4,5-bA]dithio-phene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl) carbonyl] thieno[3,4-b]-thiophenediyl] (PTB7) and [6,6]-phenyl-C(70)butyric acid methyl ester (PC70BM), which were encapsulated by the SiNx/SiOxNy hybrid barrier film, the power-conversion efficiency remained above 86% of the initial value even after 2000 h of storage in air, which is comparable to that obtained for a device encapsulated by a glass lid.